2016
DOI: 10.1007/s10897-016-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

What Do Parents of Children with Down Syndrome Think about Non‐Invasive Prenatal Testing (NIPT)?

Abstract: This study explores the attitudes of parents of children with Down syndrome towards non-invasive prenatal testing (NIPT) and widening the scope of prenatal screening. Three focus groups (n = 16) and eleven individual interviews with Dutch parents (and two relatives) of children with Down syndrome were conducted. Safety, accuracy and earlier testing were seen as the advantages of NIPT. Some participants were critical about the practice of screening for Down syndrome, but acknowledged that NIPT enables people to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 34 publications
1
69
0
Order By: Relevance
“…The three clusters of versions of routinisation are not separated but relate to and reinforce each other16: an increase in uptake of first-trimester prenatal screening might lead to an increase in abortions, which might lead to fewer children with Down’s syndrome. This might have consequences for the existing group of people with Down’s syndrome, including discrimination or less or lower quality healthcare.…”
Section: Different Interpretations Of Routinisation In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The three clusters of versions of routinisation are not separated but relate to and reinforce each other16: an increase in uptake of first-trimester prenatal screening might lead to an increase in abortions, which might lead to fewer children with Down’s syndrome. This might have consequences for the existing group of people with Down’s syndrome, including discrimination or less or lower quality healthcare.…”
Section: Different Interpretations Of Routinisation In the Literaturementioning
confidence: 99%
“…These consequences might also have implications for women’s freedom to choose or decline prenatal screening. The existence of only limited (health)care for people with Down’s syndrome or of a negative public image of Down’s syndrome could pressure women into choosing prenatal screening and into abortions of affected pregnancies 16. Routinisation as used in the literature can thus also refer to more than one version at the same time and these versions can be inter-related or affect one another.…”
Section: Different Interpretations Of Routinisation In the Literaturementioning
confidence: 99%
“…In a similar manner, parents of children with DS in other countries also had a wide spectrum of views concerning NIPS and screening for DS (Bryant et al, ; Inglis et al, ; van Schendel et al, ; Skotko et al, ). While some recognized the advantages of NIPS, it was seen by others as having potentially negative implications like increased social stigma and decreased availability of services for individuals with DS, as well as increasing the pressure on women to test.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the question is how accurate information about living with the condition of DS may affect women's informed choices. A qualitative study on effects of NIPT on the prevalence of DS in the Netherlands found that parents of children with DS think accurate information is lacking for both users and providers (Van Schendel et al, ). Similar studies in other countries support these findings.…”
Section: Testing For Down Syndromementioning
confidence: 99%